2018
DOI: 10.1063/1.5044667
|View full text |Cite
|
Sign up to set email alerts
|

Impact of iodine antisite (IPb) defects on the electronic properties of the (110) CH3NH3PbI3 surface

Abstract: The power conversion efficiency of perovskite solar cells can be significantly improved if recombination losses and hysteresis effects, often caused by the presence of structural and chemical defects present at grain boundaries and interfaces, can be minimized during the processing of photoactive layers. As a crucial first step to address this issue, we performed density functional theory calculations to evaluate the electronic structure of the energetically favored (110) perovskite surface in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Conversely, defects on the perovskite surface can potentially alter the local atomic arrangement of the surface and conclusively affect its nature. [99] PbI anti-site defect (i.e., Pb I and I Pb ) is the most anticipated deep trap in perovskite because the presence of anti-site defects introduces covalent bonds, resulting in the formation of new bonds between the defect atoms and other chemicals, thereby forming electron trap states in the bandgap region. [99] It has been shown that the formation of Pb I defect on the surface can Reproduced with permission.…”
Section: Surface Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, defects on the perovskite surface can potentially alter the local atomic arrangement of the surface and conclusively affect its nature. [99] PbI anti-site defect (i.e., Pb I and I Pb ) is the most anticipated deep trap in perovskite because the presence of anti-site defects introduces covalent bonds, resulting in the formation of new bonds between the defect atoms and other chemicals, thereby forming electron trap states in the bandgap region. [99] It has been shown that the formation of Pb I defect on the surface can Reproduced with permission.…”
Section: Surface Defectsmentioning
confidence: 99%
“…[99] PbI anti-site defect (i.e., Pb I and I Pb ) is the most anticipated deep trap in perovskite because the presence of anti-site defects introduces covalent bonds, resulting in the formation of new bonds between the defect atoms and other chemicals, thereby forming electron trap states in the bandgap region. [99] It has been shown that the formation of Pb I defect on the surface can Reproduced with permission. [87] Copyright 2017, American Chemical Society Publications.…”
Section: Surface Defectsmentioning
confidence: 99%
“…It is reported that the nature of the defect state is strongly correlated with the atomic structure of the cluster‐terminated surface. [ 34,67 ] The potential shallow defect generated from the Pb I antisite is the domination of ionic defects on the surface, which is could primarily be responsible for the loss in V oc . [ 36,68 ] Therefore, it is suggested that the treatment of OIHP film with QDs‐Cs5 is able to effectively suppress Pb I antistite defects at the surface via QDs solid‐state interdiffusion.…”
Section: Figurementioning
confidence: 99%
“…Uratani et al reported evidence of the presence of surface defects leading to trapping electrons 36 . The halide vacancy is one of the most common defects and several studies revealed that the iodine and bromine vacancies resulted in the formation of charge trapping [37][38][39][40][41] .…”
Section: Toc Graphicsmentioning
confidence: 99%